2011
DOI: 10.1103/physrevb.84.100509
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the dual nature of magnetism in iron pnictides and iron chalcogenides using x-ray emission spectroscopy

Abstract: We report Fe Kβ x-ray emission spectroscopy study of local magnetic moments in various iron based superconductors in their paramagnetic phases. Local magnetic moments are found in all samples studied: PrFeAsO, Ba(Fe, Co)2As2, LiFeAs, Fe1+x(Te,Se), and A2Fe4Se5 (A=K, Rb, and Cs). The moment size varies significantly across different families. Specifically, all iron pnictides samples have local moments of about 1 µB/Fe, while FeTe and K2Fe4Se5 families have much larger local moments of ∼ 2µB /Fe, ∼ 3.3µB /Fe, re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 47 publications
(50 reference statements)
11
97
1
1
Order By: Relevance
“…The moments detected by core level photoemission spectroscopy (PES) [158] and x-ray emission spectroscopy (XES) [157] are larger than those measured by INS. However the different results of these techniques suggest fast fluctuations of the atomic spin, beyond the localised model [148].…”
Section: B Antiferromagnetism From Localised Spinsmentioning
confidence: 89%
See 1 more Smart Citation
“…The moments detected by core level photoemission spectroscopy (PES) [158] and x-ray emission spectroscopy (XES) [157] are larger than those measured by INS. However the different results of these techniques suggest fast fluctuations of the atomic spin, beyond the localised model [148].…”
Section: B Antiferromagnetism From Localised Spinsmentioning
confidence: 89%
“…Inelastic neutron scattering (INS) and X-ray experiments have detected spin waves up to energies above 200 meV [7,[153][154][155], larger than predicted by weak coupling approaches [156] and estimated total moments larger than those expected in the weak coupling model [3,7,136,148,157,158] which do not seem to change much with increasing temperatures up to T ∼ 2T N , well above the Néel temperature. This magnetic moment is not only large in systems with magnetic order, but also in compounds which do not order magnetically as LiFeAs or Ba 0.6 K 0.4 Fe 2 As 2 [148].…”
Section: A Weak Coupling Description Of Magnetismmentioning
confidence: 99%
“…This is much smaller than the spin moment of 4.9 m B expected in the magnetic state of a free Fe 2 þ ion. The exact numbers of local moments of magnetic defects inside the iron-pnictide materials are difficult to estimate, but recent X-ray emission spectroscopy measurements revealed that the instantaneous local moments in various iron pnictides are always about 1 m B per Fe, and for the BaFe 2 As 2 case B1.3 m B per Fe has been found 39 . Thus it is expected that the moment of the order of 1 m B per defect would appear if the defects act as magnetic impurities, which can be ruled out by our results of the lack of a Curie upturn within the B0.2 m B resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Early considerations based on Fermi surface nesting provided a robust starting point to rationalize their properties. However, the effect of repulsion between electrons cannot be neglected [6] as exemplified by the existence of large magnetic moments at room temperature [8,9], superconducting materials without hole pockets [10], as well as unexpectedly complex spin arrangements [7]. Electronic correlation effects must be incorporated to understand the plethora of challenging results that experiments are rapidly unveiling.…”
Section: Introductionmentioning
confidence: 99%